Ethnicity predicts viral rebound after travel to the tropics in HIV‐infected travelers to the tropics in the Swiss HIV Cohort Study. Issue 8 (1st March 2017) - Gebreselassie, HM; Kraus, D; Fux, CA; Haubitz, S; Scherrer, A; Hatz, C; Veit, O; Stoeckle, M; Fehr, J; de Lucia, S; Cavassini, M; Bernasconi, E; et al.
Abstract : Objectives: The number of HIV‐infected individuals from developed countries travelling to tropical and subtropical areas has increased as a result of the clinical and survival benefits of combination antiretroviral therapy. The aim of our study was to describe the traveler population in the SHCS and to determine the frequency of viral rebound in virologically suppressed individuals after a travel episode to the tropics compared to non‐travelers. Methods: Swiss HIV Cohort Study participants with at least one follow‐up visit between 1 January 1989 and 28 February 2015 were eligible for inclusion in the study. The primary outcome was the occurrence of viral rebound (viral load > 200 HIV‐1 RNA copies/mL) after a travel episode compared with a nontravel episode in previously suppressed individuals (≤ 200 copies/mL). All virologically suppressed patients contributed multiple travel or nontravel episodes to the analysis. Logistic regression was performed including factors associated with viral rebound. Results: We included 16 635 patients in the study, of whom 6084 (36.5%) had ever travelled to the tropics. Travel frequency increased over time, with travellers showing better HIV parameters than nontravellers [less advanced Centers for Disease Control and Prevention (CDC) stage and higher CD4 count nadir]. Viral rebound was seen in 477 (3.9%) of 12 265 travel episodes and in 5121 (4.5%) of 114 884 nontravel episodes [unadjusted odds ratio (OR) 0.87; 95% confidence interval (CI) 0.78–0.97]. Among these 477 post‐travel viral rebounds, 115 had a resistance test performed and 51 (44%) of these showed new resistance mutations. Compared with European and North American patients, the odds for viral rebound were significantly lower in Southeast Asian (OR 0.67; 95% CI 0.51–0.88) and higher in sub‐Saharan African (SSA) patients (OR 1.41; 95% CI 1.22–1.62). Travel further increased the odds of viral rebound in SSA patients (OR 2.00; 95% CI 1.53–2.61). Conclusions: Region of origin is the main risk factor for viral rebound rather than travel per se . Pre‐travel adherence counselling should focus on patients of SSA origin.